Gammaherpesvirus Infection Stimulates Lung Tumor-Promoting Inflammation - Sudurika S. Mukhopadhyay; Kenneth F. Swan; Gabriella Pridjian; Jay K. Kolls; Yan Zhuang; Qinyan Yin; Joseph A. Lasky; Erik Flemington; Cindy A. Morris; Zhen Lin; Gilbert F. Morris (Pathogens)
Lung tumor-promoting environmental exposures and γherpesvirus infections are associated with Type 17 inflammation. To test the effect of γherpesvirus infection in promoting lung tumorigenesis, we infected mutant K-Ras-expressing (K-RasLA1) mice with the murine γherpesvirus MHV68 via oropharyngeal aspiration. After 7 weeks, the infected mice displayed a more than 2-fold increase in lung tumors relative to their K-RasLA1 uninfected littermates. Assessment of cytokines in the lung revealed that expression of Type 17 cytokines (Il-6, Cxcl1, Csf3) peaked at day 7 post-infection. These observations correlated with the post-infection appearance of known immune mediators of tumor promotion via IL-17A in the lungs of tumor-bearing mice. Surprisingly, Cd84, an immune cell marker mRNA, did not increase in MHV68-infected wild-type mice lacking lung tumors. Csf3 and Cxcl1 protein levels increased more in the lungs of infected K-RasLA1 mice relative to infected wild-type littermates. Flow cytometric and transcriptomic analyses indicated that the infected K-RasLA1 mice had increased Ly6Gdim/Ly6Chi immune cells in the lung relative to levels seen in uninfected control K-RasLA1 mice. Selective methylation of adenosines (m6A modification) in immune-cell-enriched mRNAs appeared to correlate with inflammatory infiltrates in the lung. These observations implicate γherpesvirus infection in lung tumor promotion and selective accumulation of immune cells in the lung that appears to be associated with m6A modification of mRNAs in those cells.